Invasive Microsporum canis causing rhinitis and stomatitis in a cat. (8th April 2016) - Ziglioli, V.; Panciera, D. L.; LeRoith, T.; Wiederhold, N.; Sutton, D.
Abstract : Microsporum canis is a pathogenic fungus that typically causes dermatophytosis in cats. This report describes a cat with a Microsporum canis infection causing invasive fungal rhinitis that extended through the hard palate, resulting in adjacent stomatitis. Treatment with itraconazole and terbinafine resolved the infection.